Child-Protection Systems – Slovakian Perspective - Koromház, Peter (Child-Protection Systems, 2025)
Abstract:The protection of minors and the safeguarding of their best interests constitute a fundamental principle of family law in the Slovak Republic. This chapter examines the relevant substantive and procedural legal frameworks that embody this principle within the Slovak legal system. The analysis is primarily focused on the current legislative provisions governing the protection of minors and the family, with particular emphasis on the legal regulation of alternative care for minors, the institution of adoption, and the structural organization of the system of social and legal protection of children and social guardianship. Further attention is devoted to the system of state-provided support for children, families, and persons with disabilities, particularly in the form of financial allowances and benefits granted not only to parents and children but also to persons entrusted with the provision of alternative care for minors. The chapter concludes with an examination of the Commissioner for Children’s Office, which serves as the institutional authority responsible for monitoring the observance and enforcement of children’s rights within the Slovak Republic. Keywords: the best interests of the child, alternative care, adoption, urgent measure, contribution